How big is China's real estate bubble and why hasn't it burst yet?. (May 2017) - Zhao, Simon X.B.; Zhan, Hongyu; Jiang, Yanpeng; Pan, Wenjun
Highlights: We examined the relationship between financial crises and real estate development. Illustrating the ways real estate crises develop into financial crises. A financial crisis often emerges from a weak financial system. The consequences of China's real estate bubble could result in economic hard landing. Abstract: This paper represents an international, comparative, empirical study of the relationship between financial crises and real estate development, with a focus on China. We review recent major crises around the world from 1980 to 2014.We then discuss the ways real estate crises develop into financial crises (considering that most recent financial crises actually trace their origins to real estate bubbles). We also look at China's current economic situation, and identify potential threats to the country's economic development by comparing it with other countries' historical experiences. A comprehensive analysis of the relationship between real estate and finance predicts an upcoming burst in China's bubble economy. We explore the deep-seated underlying Chinese systemic causes and characteristics that explain why China's economic bubble has yet to burst and the possible financial consequences of the real estate bubble in China. Our findings suggest that a financial crisis often emerges from a weak financial system which is too closely linked to the country's real estate sector. These linkages allow real estate crises to mushroom into financial crises. In turn, these financial crises balloon into macroeconomic crises. China's current situation is extremely alarming, though the country shows remarkable resilience to crisis as the government seems to possess the tools and capacity to avoid a hard landing. The findings of this research advance our understanding of the consequences of China's real estate bubble and sound a clear warning to China's policymakers.